Zgodnje obdobje slovenske ekspresionistične kratke proze in njene slogovne prvine - Čeh Steger, Jožica (Slavia Centralis, 2020)
Early Slovene Expressionist short narrative prose and its stylistic featuresRecent studies have shown that the beginnings of Slovene expressionist short prose overlap with the beginning of the First World War, when alongside Cankar’s "podobe iz sanj (images from dreams)", a younger generation of writers (France Bevk, Stanko Majcen, Ivan Dornik, Narte Velikonja, etc.) began publishing distorted psychological short stories in the Journal Dom in svet (Home and World) containing ethical judgments of war. The present contribution focuses on various stylistic procedures and especially on the model of ominous dreams associated with Cankar’s symbolic-allegorical and metaphoric "images", and on Bevk’s war short story involving characteristic parabolic procedures, while its entry into the expressionist stylistic paradigm is evident in dissonance, grotesque images, abstract use of colours, and rhetorical speech.
Keywords: expressionism; short prose; style; Ivan Cankar; France Bevk